Electron impact transfer rates between metastable and resonant states of argon investigated by laser pump–probe technique. (29th September 2015) - Carbone, Emile; van Veldhuizen, Eddie; Kroesen, Gerrit; Sadeghi, Nader
Abstract: The laser pump–probe technique is used to study the electron impact transfer between the 1s5 and 1s4 states of argon (in Paschen's notation) belonging to the 2 P3/2 ion core for electron temperatures in the range of 1–2 eV. A rate coefficient of m 3 s −1 is determined for the transfer from 1s5 to 1s4 state. Different pumping schemes between the 1s and 2p states but also 3p states are used to verify the obtained value but also to probe the transfers with ion-core change toward the 2 P1/2 ion-core. Our results show the presence of an important transfer channel between 1s2 and 1s4 states, and a rate coefficient of m 3 s −1 is estimated for this transfer. The present results confirm that recent quantum mechanical calculations by Zatsarinny et al [001 ] underestimate significantly the cross sections for electron impact transfers between 1s states of argon.